PERFORMANCE MEASUREMENT OF DYNAMIC CONTROL FOR PISTON TRAJECTORY IN A FREE-PISTON LINEAR ELECTRIC GENERATOR BY LOAD CURRENT MODULATION - BASHIR, AHSAN (2023)
A sustained, continuous operation of a free-piston linear engine-generator (FPLG) requires sufficient compression ratio, displacement and speed of single-moving piston assembly for combustion to occur. The problem arises due to inherent characteristics of the FPLG, which are inconsistent displacement endpoints, absence of mechanical flywheel and no misfire support. Piston motion in an FPLG is dynamically coupled to and governed by balance of forces and energy between combustion and generation processes. The free-piston nature and absence of mechanical flywheel lead to a condition of irregular and unassisted piston motion, which can cause operation stoppage. Installation of an auxiliary mechanical system to assist piston motion and counter misfires is impractical. Assistance in the form of electrical energy is the only viable solution, considering the device is an electric generator with accessible stored electrical energy.